Manipulating exercise order affects muscular performance during a resistance exercise training session - Sforzo, G. A.; Touey, P. R. (The Journal of Strength and Conditioning Research, 1996)
Sforzo et al (1) examined the effects of the order of exercises on performance during a resistance training session. 17 trained subjects performed 2 weight training sessions. In the first session, exercises proceeded from structural exercises to body part (squat, leg extension, leg flexion, bench press, military press, and triceps pushdown). In the second session performed a few days later, exercises proceeded in the opposite order (leg flexion, leg extension, squat, triceps pushdown, military press, bench press). 4 sets of 8 repetitions per exercise were performed with 2 minutes rest between sets. Total force (TF = resistance x repetitions) was measured for each exercise. Fatigue rate (FR = TFset1 - TFset4/TFset1 * 100%) was also measured FINDINGS: TF for the bench press was significantly lower when it was preceded by the triceps pushdown and the military press. TF for squats, leg extensions, and triceps pushdown were greatest when performed first in the exercise session. TF for the entire training session was highest when exercise order went from structural to body part. FR for the bench press was significantly lower when exercises went from body part to structural. IMPLICATIONS: The order of exercises effects performance during a resistance training session. If an individual wants to maximize stimulation for a certain muscle group, exercises for that muscle group should be performed first in the session. If an individual wants to maximize performance on a certain lift, than that lift should be performed first in a training session. Finally, athletes looking to maximize the stimulus for all body parts during a training session should perform large muscle-mass, structural exercises first, and then follow those exercises with smaller isolation movements.